2016
DOI: 10.1007/s00221-016-4778-2
|View full text |Cite
|
Sign up to set email alerts
|

Turning perception on its head: cephalic perception of whole and partial length of a wielded object

Abstract: Flexibility is a fundamental hallmark of perceptual systems. In particular, there is a great deal of flexibility in the ability to perceive properties of occluded objects by effortful or dynamic touch-hefting, wielding, or otherwise manipulating those objects by muscular effort. Perception of length of an occluded wielded object is comparable when that object is wielded by anatomical components that differ in sensitivity, dexterity, and functionality. Moreover, perception of this property is supported by an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Previous research has found evidence of both task-specificity and anatomical independence in perception of properties of wielded objects. In particular, people can direct attention to different exteroceptive properties of wielded object (e.g., object length), and perception of such properties remains invariant across transformations including the anatomical component used to wield the object (see Hajnal, Fonseca, Harrison, et al, 2007a;Wagman et al, 2017). Such flexibility is grounded in sensitivity to task-specific (in this case, exterospecific) components of an invariant mechanical stimulation pattern-the rotational inertia (I) of the person-object system.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research has found evidence of both task-specificity and anatomical independence in perception of properties of wielded objects. In particular, people can direct attention to different exteroceptive properties of wielded object (e.g., object length), and perception of such properties remains invariant across transformations including the anatomical component used to wield the object (see Hajnal, Fonseca, Harrison, et al, 2007a;Wagman et al, 2017). Such flexibility is grounded in sensitivity to task-specific (in this case, exterospecific) components of an invariant mechanical stimulation pattern-the rotational inertia (I) of the person-object system.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments have shown (1) that people can perceive exteroceptive properties of an object wielded with the hand (e.g., whole or partial length of that object), (2) that these abilities generalize to objects wielded by other body parts (including the foot, the torso, and the head), and (3) that perception of such properties is supported by analogous sensitivities to exterospecific components of I across anatomical components (Hajnal, Fonseca, Kinsella-Shaw, et al, 2007b;Palatinus et al, 2011;Wagman et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations